Pancreatoenteral anastomosis or direct closure of the pancreatic remnant after a distal pancreatectomy: a single-centre experience - Klein, Fritz (Blackwell Publishing Ltd, 2012)
BACKGROUND: A major complication of a distal pancreatectomy (DP) is the formation of a post-operative pancreatic fistula (POPF). In spite of the utilization of numerous surgical techniques no consensus on an appropriate technique for closure of the pancreatic remnant after DP has been established yet. The aim of this study was to analyse the impact of pancreatoenteral anastomosis (PE) vs. direct closure (DC) of the pancreatic remnant on POPF. METHODS: A total of 198 consecutive patients who underwent a distal pancreatectomy between 2002 and 2010 at our institution were retrospectively analysed for post-operative morbidity and mortality. RESULTS: One hundred and fifty-one patients (76.3%) received DC whereas PE was performed in 47 patients (23.7%). The incidence of POPF was higher in the DC group (22% vs. 11%), whereas the rate of post-operative haemorrhage was higher in the PE group (11% vs. 7%). However, these differences were not significant. Additionally, there were no significant differences in overall post-operative morbidity and mortality between the groups. CONCLUSIONS: The performance of PE instead of DC may be considered as a safe alternative in individual patients, but it does not significantly lead to a general improvement in post-operative outcome after DP. An interdisciplinary collaboration in the prevention and treatment of POPF therefore remains essential.